Komplexe Sachverhalte erfolgreich kommunizieren: eine Studie zur vereinfachten Darstellung des Themas Wasserstoff im deutschen Energiewendediskurs, mit besonderem Blick auf Leichte Sprache und Multimodalität - Iris Jammernegg (MediAzioni)
This article investigates on one hand the interrelationship between simplification, the need for comprehensibility and the communication goals pursued by the respective senders, and on the other, those between intralingual translation and (technical) writing. Special attention is paid to recipient-oriented linguistic design in relation to multimodal and textual aspects. The analysis focuses mainly on how, and for which target audiences, German energy discourse addresses the topic pertaining to the importance of hydrogen for energy transition – a topic which is both technically complex and socio-politically and economically relevant. For this purpose, I have collected a corpus that combines online texts of selected actors who are active in the energy sector or who are supposed to facilitate the energy transition. The focus is on the different linguistic, visual and textual strategies and means employed to simplify the given complexity in such a way that the relevant target groups, which range from citizens interested in the topic to active or potential customers and people with cognitive impairments, can understand the content according to the broadcaster's intentions. In this respect, a comparison between messages by the same actor in both standard language and easy language proves to be particularly illuminating.